On the Rationality of Network Development: the Case of the Belgian Highway Network - Vanoutrive, Thomas; Van Damme, Ilja; De Block, Greet (International Planning History Society Proceedings, 2016)
The development of transport networks has been explained, predicted and planned using a variety of methodological approaches. These range from narrative historical accounts to the application of models borrowed from the natural sciences, the latter being predominant in the field of transport economics. Probably the most remarkable example is the mimicking of highway networks by slime mould in Petri dishes. The aim of this paper is to examine and compare methods used to hypothesise on and explain the development of transport networks, and we specifically focus on methods that emphasise topology over topography, relations over form (in line with the work of Gabriel Dupuy and others). Belgium was chosen as case because the topology of Belgium’s highway network is considered by some as one of the most ‘rational’ in the world, although its form and materiality are often qualified as ‘chaotic’, or indeed ‘irrational’. The quantitative analysis of the development of this network reported in the present paper indicates that this supposed rationality is seldom followed and seemingly ‘irrational’ parameters literally deviate its growth. Therefore, the quantitative part is complemented by a historical analysis which focuses more on the role, and indeed rationality, of historical actors and the wider institutional context. Material provided by this case study supplies fuel for discussion about broader issues, in particular the underlying ideological and political-economic claims associated with a particular methodological approach. This is especially relevant given the fact that models used to predict past transport investments are also employed to evaluate future investments in infrastructure. Quantitative approaches generally attribute a central role to the concept of demand, and thus degrees of ‘rationality’ are in fact linked to ideas of consumer democracy where individual demand guides investment decisions. In contrast, interpretations of a less deterministic nature emphasise the degrees of freedom of political actors/choice. We conclude that the views held by actors of the past, present and future of transport networks are relevant for democratic debates on transport policy since the metaphors and models used are not value-neutral.